The Influence of Physical Tuning Technology on Voice Over LTE (VoLTE) - zurnawita, zurnawita; Chandra, Dikky; zulya, fajru ju (JITCE (Journal of Information Technology and Computer Engineering), 2024)
The Long-Term Evolution (LTE) technology is currently evolving in the cellular communication system. Currently, LTE technology is only used for faster internet data activities. Unfortunately, phone calls still rely on second-generation (2G) or third-generation (3G) networks. To improve the quality of voice calls, one of the ways is through the utilization of Voice Over LTE (VoLTE) technology. The reason for using VoLTE in fourth-generation (4G) networks includes the voice quality based on Internet Protocol (IP). This study analyzes the performance of VoLTE technology networks. Based on the data collected, the Reference Signal Received Power (RSRP) with a percentage of 37.73% falls into the Good category, Signal to Interference Noise Ratio (SINR) with a percentage of 55.32% falls into the Fair category, and Throughput with a percentage of 66.16% falls into the Poor category. In terms of delay, it has a score of 4, categorized as very good, jitter has a score of 3, categorized as good, and packet loss has a score of 4, categorized as very good. The optimization results using physical tuning show that the Reference Signal Received Power (RSRP) falls into the Good category with a percentage of 52.8%, Signal to Interference Noise Ratio (SINR) falls into the Good category with a percentage of 70%, and Throughput falls into the Very Good category with a percentage of 64.50%.